Pelatihan Penyusunan Instrumen Diagnostik Multitier untuk Mengatasi Miskonsepsi Siswa pada Kelompok MGMP Kimia Kabupaten Sidoarjo - Widarti, Hayuni Retno; Herunata, Herunata; Parlan, Parlan; Robi'ah, Syauqiya Afnanur; Rokhim, Deni Ainur (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2026)
Misconceptions in chemistry learning frequently occur because many topics are abstract and difficult for students to understand. This condition requires teachers to have a thorough understanding of difficult concepts as well as appropriate strategies to identify and address misconceptions. Based on this need, the community service team conducted a training program aimed at enhancing chemistry teachers’ understanding of difficult concepts, misconceptions, and the development of multitier diagnostic instruments. The activity was implemented through a combination of online and offline sessions in collaboration with chemistry teachers from the MGMP (Subject Teacher Forum) of Sidoarjo Regency. The implementation methods included lectures, interactive discussions, and hands-on practice in designing diagnostic instruments. The training materials covered the characteristics of difficult concepts, causes of misconceptions, strategies for overcoming them, and the application of various misconception identification instruments such as multitier diagnostic tests, interviews, concept maps, and open-ended tests. The evaluation of the activity was carried out using pre- and post-training questionnaires as well as practical assignments on instrument development. The results showed that participants responded positively to the training activities and reported improved understanding and skills in designing diagnostic instruments to identify students’ misconceptions. In addition, participants were able to produce multitier diagnostic instrument designs in accordance with the training provided. Keywords: Chemistry Teachers, Misconceptions, Difficult Concepts, Diagnostic Instruments. Miskonsepsi dalam pelajaran kimia sering terjadi karena banyak materi yang sifatnya abstrak dan sulit dipahami oleh siswa. Kondisi ini menuntut guru untuk memiliki pemahaman yang mendalam mengenai konsep sukar serta strategi tepat dalam mengidentifikasi dan mengatasi miskonsepsi. Berdasarkan kebutuhan tersebut, tim pengabdian melaksanakan kegiatan pelatihan dengan tema peningkatan pemahaman guru kimia terhadap konsep sukar, miskonsepsi, dan penyusunan instrumen diagnostik multitier. Kegiatan dilaksanakan dalam bentuk kombinasi daring dan luring bersama mitra guru MGMP Kimia Kabupaten Sidoarjo. Metode pelaksanaan meliputi ceramah, diskusi interaktif, serta praktik langsung penyusunan instrumen diagnostik. Materi pelatihan mencakup penjelasan tentang karakteristik konsep sukar, penyebab miskonsepsi, strategi penanggulangannya, serta penerapan berbagai instrumen identifikasi seperti tes multitier, wawancara, peta konsep, dan soal terbuka (open-ended test). Evaluasi kegiatan dilakukan melalui angket pra dan pascapelatihan, serta penugasan praktik penyusunan instrumen. Hasil kegiatan menunjukkan bahwa peserta memberikan respons positif terhadap pelaksanaan pelatihan dan menyatakan memperoleh pemahaman serta keterampilan yang lebih baik dalam merancang instrumen diagnostik untuk mengidentifikasi miskonsepsi. Peserta juga mampu menghasilkan rancangan instrumen diagnostik multitier sesuai dengan pelatihan yang telah diajarkan. Kata Kunci: Guru Kimia, Miskonsepsi, Konsep Sukar, Instrumen Diagnostik